An ontology to support the classification of learning material in an organizational learning environment: An evaluation. Issue 1 (18th April 2017) - Valaski, Joselaine; Reinehr, Sheila; Malucelli, Andreia
Abstract : Purpose: The purpose of this research was to evaluate whether ontology integrated in an organizational learning environment may support the automatic learning material classification in a specific knowledge area. Design/methodology/approach: An ontology for recommending learning material was integrated in the organizational learning environment based on ontology. An experiment was performed with 15 experts and 84 learners. Experts and learners were asked to classify 30 learning material related to Software Engineering area. The results obtained from experts and learners were compared with the ontology results. Findings: Among 30 learning materials evaluated, 24 learning materials got closer to the expert classification using the ontology than using the learners' manual classification. The learners had difficulties in correctly classifying the learning materials according to the knowledge area applied. Originality/value: In an autonomous collaborative environment without a tutor responsible for organizing the learning materials shared by collaborators, an ontology may be an auxiliary mechanism to support automatic learning material classification. The proposed ontology uses recommendations given by the collaborators to get the correct knowledge area classification. The correct classification may support retrieval of appropriate learning materials according to the learners' needs.